ACCOUNTING FRAUD IN VILLAGE CREDIT INSTITUTION (LPD) IN DENPASAR CITY - Ida Ayu Budhananda Munidewi; Ni Nyoman Ayu Suryandari; I Made Suryawan (AIBPM Publisher, 2019)
The importance of financial statements for a company causes financial statements to be prepared accurately and according to accounting rules. In fact there are still irregularities in the financial statements so that information becomes irrelevant and unreliable. This deviation is one of the accounting fraudulent actions. With the high risk of fraud on financial statements, it is necessary to study related trends in accounting fraud. The results of the study indicate that the effectiveness of internal control has a positive effect on the tendency of accounting fraud. While information asymmetry, compliance with accounting rules and management morality does not affect the tendency of accounting fraud in village credit institution.